Legal Study of Legal Treatment of Prisoners of War in the Perspective of Humanitarian Law: Legal Study of Legal Treatment of Prisoners of War in the Perspective of Humanitarian Law - Edwin; Tri Agus Suswantoro; Ahmad Jaeni; Tiarsen Buaton (Faculty of Law, Universitas Pekalongan, 2025)
Enforcement prisoner wars waged onevery country are inseparable from provisions ofhumanitarian law. Every country involved in theorigination convention subject to the established ruleseven has been implemented well. Aims: From thebackground that has been described above, then writerinterested in raising this material in the creation of ajournal with the title